Ethnomathematics: Mathematical Aspects of Panjalin Traditional House and Its Relation to Learning in Schools - Sulaiman, Herri; Nasir, Fuad (Al-Jabar: Jurnal Pendidikan Matematika, 2020)
This study was aimed to improve the learning process at school through ethnomathematics culture-based learning, namely the Panjalin traditional house. The purpose of this study was to explore the culture of Panjalin society as a medium for learning mathematics. Through culture-based learning, students were expected to improve their mathematics learning outcomes. The results showed that there were mathematical concepts and activities in the Panjalin traditional house. Students should learn the theories about mathematical concepts and know their application. The result of the study was aimed to examine the aspects of mathematics in the Panjalin traditional house and its relationship with mathematics learning at schools.